2014
DOI: 10.3382/ps.2013-03600
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of juvenile Leghorn chickens to lead acetate enhances antibiotic resistance in enteric bacterial flora

Abstract: Heavy metals have been implicated for their ability to increase antibiotic resistance in bacteria collected from polluted waters, independent of antibiotic exposure. Specific-pathogen-free Leghorn chickens were therefore given Pb acetate in the drinking water to expose the enteric bacteria to Pb and to determine if antibiotic resistance changed in these bacteria. Concentrations of Pb used were 0.0, 0.01, 0.1, 1.0, or 10.0 mM; birds given the highest 2 concentrations showed signs of moribundity and dehydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Arsenic cycling has been suggested to be a prominent feature in ancient microbial mats over 2.7 billion years old ( Sforna et al, 2014 ). Our data from Pavilion Lake microbialites suggest that heavy-metal resistance could be a general feature of microbialites globally, which may also provide cross-protection against antibiotics ( Nisanian et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic cycling has been suggested to be a prominent feature in ancient microbial mats over 2.7 billion years old ( Sforna et al, 2014 ). Our data from Pavilion Lake microbialites suggest that heavy-metal resistance could be a general feature of microbialites globally, which may also provide cross-protection against antibiotics ( Nisanian et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Heavy-metal resistance genes may be involved in resistance, homeostasis or sequestration of metals. Antibiotic resistance has also been linked to heavy-metal stress, suggesting that resistance to one can lead to resistance to the other in complex bacterial communities ( Nisanian et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these genes, however, are associated with conjugative transposons (e.g., Tn 917 and the Tn 916–1525 family), which are often associated with multiple resistance (Roberts 2012). Beta-lactam resistance has been associated with mercury (e.g., Fraser 1971; Richmond et al 1964) and copper (e.g., Knapp et al 2011) exposure, and lead exposure contributed to AR in enteric bacteria in poultry (Nisanian et al 2014). The results from our study indicate linkage with other metals, namely aluminium, manganese, uranium and lead.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond studies of co-election in environmental media, studies on Staphylococcus isolates from animals and humans have shown associations between Pb and Cd resistance and antibiotic resistance [ 26 , 27 ]. For example, fecal bacterial isolates from leghorn chickens that were fed Pb at levels that did not cause other morbidity or mortality, showed significantly elevated levels of antibiotic resistance compared to controls, and demonstrated a dose response relationship within different levels of Pb in the diet [ 28 ]. However, to our knowledge, few if any studies have examined the relationship between Pb or Cd exposure and selection for antibiotic resistance in humans.…”
Section: Introductionmentioning
confidence: 99%